Curator's work during the adaptation period of students at the Kharkiv National Automobile and Road University - Nenastina, T.; Berezhna, K.; Bugaevskyi, S. (New Collegium, 2023)
Due to the transition to the new generation of educational standards and the increase in hours for independent work, there is a need to train a creative, active person who can independently choose his own life path. The educational process in the life of the university is planned and organized along with studies and scientific activities. The curator of the academic group is usually assigned an experimental teacher, since this position includes responsible and thorough work, which should take into account the profile of training of specialists and the specifics of the faculty. Students' problems related to the educational process at the university, interpersonal conflicts and relations in the group, and the question of the student group participation in the public and cultural mass activities of the university are resolved by the curator. The effectiveness of the educational work of the curator of the academic group is largely determined by its planning. Based on the analysis of theoretical studies and the experience of modern pedagogues-practitioners, the roles and functions of the curator in working with the group are defined, the curator's duties are described, and an approximate plan for the work of curators in universities is proposed. The views on the organization of educational work in higher education are presented. The creation of new mechanisms related to the selectivity of some disciplines makes it necessary to carry out additional explanatory and advisory work of curators regarding the formation of individual study plans for applicants. It is shown that the curator uses various forms of educational work in his activities, which contribute to the formation of the personality of the future specialist as a patriot citizen, who cares about the fate of the Ukrainian state, law, and order, education, and culture.